Role of Remittance in Economic Development of Nepal - Srivastava, Nagendra Lal; Chaudhary, Shashi K. (Journal of Nepalese Business Studies, 2008)
This article deals with the analysis of direct impact of remittance on three development indicators viz. GDP, GNP and PCI of the nation which are also the dependent variables of the proposed models. The analysis has been carried out with linear and log-linear models under multiple regressions. The impact of remittance has been seen most remarkable in the GDP and GNP both in nominal and real terms. In the nominal GDP and GNP, the remittance shows 61 percent and 72 percent impact respectively while in real term it shows 48 percent and 55 percent respectively. It has also shown positive impact on the PCI but it is comparatively low (four percent in nominal and one percent in real terms). The growth rates of independent variables (Rm, K, L and X) have also been tested in the same model to find the effects on the dependent variables. The findings are positive except for labor force, but they are marginal which show that remittance has not been used effectively so as to increase the real growth rates of the economy. The Journal of Nepalese Business Studies Vol. IV, No.1 (2007) pp. 28-37